Overview of game meat utilisation challenges and opportunities: A European perspective - Needham, Tersia; Bureš, Daniel; Černý, Jiří; Hoffman, Louwrens C (Meat science, 2023)
Re-wilding and similar initiatives have resulted in an increase in wildlife suitable for human consumption in Europe. However, game meat production and consumption present several challenges, including infectious diseases which pose risks to livestock, processers, and consumers. This review provides insights into the infectious diseases and toxic contaminants associated with game meat. The effect of killing method on the meat quality is also discussed and means of improving the meat quality of game meat is elucidated. The use of different food safety systems that could be applied to provide safe meat is reported. The importance of collaborative multi-sector approaches is emphasized, to generate and distribute knowledge and implement One Health strategies that ensure the safe, traceable, sustainable, and professional development of commercial game meat supply chains.
Keywords: divoká zvířata; Humans; Wild game meat; systém analýzy rizika a stanovení kritických kontrolních bodů; Hazard Analysis and Critical Control Points; lidé; Europe; zvířata; Meat; kontrola infekce; infekce; Venison; Animals, Wild; Hygiene; hygiena; maso; Consumption; Animals; Safety; Infection Control; Hunting; Evropa; Infections